Diet-induced vitamin D deficiency triggers inflammation and DNA damage profile in murine myometrium - ElHusseini H; Elkafas H; Abdelaziz M; Halder S; Atabiekov I; Eziba N; Ismail N; El Andaloussi A; Al-Hendy A (Dove Medical Press, 2018)
Heba Elhusseini,1 Hoda Elkafas,1,2 Mohamed Abdelaziz,3 Sunil Halder,1 Ihor Atabiekov,1 Noura Eziba,1 Nahed Ismail,4 Abdeljabar El Andaloussi,1 Ayman Al-Hendy1 1Department of Obstetrics and Gynecology, University of Illinois of Chicago, Chicago, IL, USA; 2Pharmacology and Toxicology Department, National Organization for Drug Control and Research, Cairo, Egypt; 3Department of Obstetrics and Gynecology, Mansoura University Hospital, Mansoura Faculty of Medicine, Mansoura, Egypt; 4Clinical Microbiology Division, University of Illinois of Chicago, Chicago, IL, USA Background: Previously, we reported a significantly higher prevalence of uterine fibroids (UFs) in African American women. This minority group also commonly suffers from vitamin D deficiency. We have demonstrated that 1,25(OH)2D3 attains a fibroid growth inhibitory impact through its ability to block the G1/S (gap 1/synthesis) phase of the cell cycle. Vitamin D is involved in DNA damage as well as in immune response regulation, anti-inflammation, autoimmunity and cancer. Since most of the prior data on vitamin D and UF were generated in vitro via established cell lines, it was necessary to verify and validate this observation in vivo using a diet-induced vitamin D-deficient mouse model. Materials and Methods: Our model of vitamin D lacking function was established using 8-week exposure of C57/BL6 mice to vitamin D-deficient diet provides evidence of different functions accomplished by vitamin D in the regulation of myometrium homeostasis disrupted in the context of uterine fibroid. Results: We found that vitamin D deficiency was associated with increased expression of sex steroid receptors in murine myometrium, increased expression of proliferation related genes, the promotion of fibrosis and enhanced inflammation, and promoted immunosuppression through Tregs expansion in murine myometrium. We also showed that a vitamin D deficient diet enhanced DNA damage in murine myometrium. Conclusion: Our model mimics the effects in humans that a lack of vitamin D has and propels the study of in vivo interaction between inflammation, genomic instability and cell proliferation in the myometrium. Keywords: vitamin D, diet, inflammation, DNA damage, uterine fibroids